Bronchoscopic long-term palliation of a recurrent atypical carcinoid tumor - Katsenos, Stamatis; Rojas-Solano, Jose; Schuhmann, Maren; Becker, Heinrich D. (Respiration, 2011)
Bronchial carcinoid tumors account for 1-2% of all primary lung tumors and are separated into 2 subgroups: typical and atypical carcinoids. Atypical carcinoids as intermediate-grade malignancies can metastasize more frequently, thus exhibiting poorer prognosis than the low-grade typical carcinoid tumors. Surgical resection remains the mainstay of treatment for pulmonary carcinoids. Bronchoscopic treatment using ablation techniques is an effective alternative to surgery in selected patients with typical carcinoid tumors. However, evidence is lacking regarding the effect of bronchoscopic resection of atypical carcinoid tumor and its recurrences. We report the case of a 73-year-old male with frequent endobronchial recurrences of a previously surgically resected atypical carcinoid tumor successfully treated using Nd:YAG laser photoresection. Furthermore, the therapeutic and local staging aspects of the disease are discussed emphasizing the efficacy of bronchoscopic resection strategies and the value of novel bronchoscopic imaging techniques in detailed inspection of the structures of the bronchial wall.
Gesehen am 21.07.2022